The discourse of dependency and the agrarian roots of welfare doctrines in Africa: The case of Botswana - Jeremy Seekings (sozialpolitik.ch, 2017)
Political elites across much of Africa have criticized welfare programmes and the idea of a welfare state for fostering dependency. Anxiety over dependency is not unique to East or Southern Africa, but the discourse of dependency in countries such as Botswana differs in important respects to the discourses of dependency articulated in some industrialised societies (notably the USA). This paper examines African discourses of dependency through a case-study of Botswana. The paper races the genealogy of dependency through programmatic responses to drought between the 1960s and 1990s, and a reaction in the 2000s. The growth of a discourse of dependency reflected both social and economic concerns: Socially, it was rooted in pre-existing understandings of the reciprocal responsibilities associated with kinship and community; economically, the emergence of a discourse of dependency reflected the rise of an approach to development rooted in nostalgic conceptions of hard-working small farmers. The discourse of dependency appealed to both conservatives (offended by anti-social individualism) and economic modernisers (eager for an explanation for the failures of the developmental project to eliminate poverty).